An improvement to linear-elastic procedures for seismic performance assessment. - Günay, Mehmet Selim (Earthquake engineering & structural dynamics.)
An improved linear-elastic analysis procedure is developed in this paper as a simple approximate method for displacement-based seismic assessment of the existing buildings. The procedure is mainly based on reducing the stiffness of structural members that are expected to respond in the inelastic range in a single global iteration step. Modal spectral displacement demands are determined from the equal displacement rule. Response predictions obtained from the proposed procedure are evaluated comparatively by using the results of benchmark nonlinear response history analysis, and both the conventional and the multi-mode pushover analyses. In comparative evaluations, a twelve-story RC plane frame and a six-story unsymmetrical-plan RC frame are employed by using 91 ground motion components. It is observed that the proposed procedure estimates the flexural deformation demands in deformation-controlled members and the shear forces in force-controlled members with reasonable accuracy.